The Government’s Responsibility for the Fulfillment of the Right to Education for Child Labour in Working Relationships - Nur Paikah; Achmad Ruslan; Marwati Riza; Iin Karita Sakharina (Indian Journal of Forensic Medicine & Toxicology, 2021)
The purpose of this study is to analyze the setting of the education right for child labour in workingrelationships. The method used in this study is empirical normative. The results showed that the regulationof the fulfillment of the education right for child labour in the working relationship have not been maximal,because there is still a legal void in the Employment Law and the absence of synchronization of Law No.20 of 2003 on the National Education System, Government Regulation No. 48/2008 on Education Funding.The implementation of the 20% education budget has not been achieved so that uneven education is enjoyed.Therefore, a revision of the rules on the fulfillment of educational rights for child labour in an integrated andharmonious working relationship is required.